Efektifitas Terapy Akupresur Terhadap Pengurangan Dismenore Pada Mahasiswa DIII Kebidanan - Uliarta Marbun; Lili Purnama sari (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction; Problems experienced by adolescents related to menstruation, dysmenorrhea is the most common gynecological complaint among adolescent and young adult women. Purpose; knowing the effectiveness of acupressure therapy against dysmenorrhea in DIII Midwifery students. Method; The research used was a pre-experimental design and a pretest-posttest design. The population is all students of the DIII Midwifery Study Program. The sample with purposive sampling technique used statistical tests through the Kolmogorov Smirnov t-test. Results; showed that acupressure therapy can reduce pain during menstruation. Conclusion; The effectiveness of giving acupressure therapy is a reduction in dysmenorrhea, a reduction in dysmenorrhea can be seen in 1 to 2 days after regular acupressure therapy is carried out.